Bibliometric analysis of the evolution of smart ports and ships: trends and challenges - Collazos-Alarcón, Mercedes Alejandrina; Tuñoque-Morante, Luis; Pisfil-Benites, Nilthon; Vidal-Taboada, Silvia Lourdes (LACCEI, 2024)
Abstract- In this research, a bibliometric analysis of research on smart ports and ships was carried out, covering the period from 1997 to 2023. The bibliometric mapping methodology and the Scopus database were used to collect 483 papers from 281 scientific journals. The results showed a significant growth in research from 2013 onwards, indicating a growing research interest in this subject. Crucial areas of research such as internet of things, decision making, and automation were identified. It also highlighted the significant international collaboration that characterizes this field. In addition, outstanding authors were identified for their notable contribution and topics to be explored in greater depth such as sustainable development and energy efficiency.